To Determine the Factors that Affect the Delay in Diagnosis of Acute Appendicitis, Affecting the Morbidity and Mortality of Patients - Syed Aamer Hussain, Mohammad Shoaib Khan, Tariq Jamil, Zakariya Rashid, Habib Un-Nabi, Abdul Wali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective/aim: To reduce the morbidity and mortality associated with acute appendicitis, our study aims to identify the factors that contribute to diagnostic delays. Method: This study is a cross-sectional analysis of data collected at a tertiary care facility in Ayyub Teaching Hospital Abbottabad and Timergara Teaching Hospital Dir Lowerover the course of a year January 2022 to June 2022. All patients over the age of 16 who presented to the emergency room with acute appendicitis two or more days after the initial attack and who gave informed consent constituted the study population. All patients under the age of 16 who presented to the emergency room with signs and symptoms of acute appendicitis earlier than two days after the initial attack were excluded from the study. Patients’ details were recorded in a standard proforma. Patients’ ages, sexes, addresses, delays, doctors’ diagnoses, and other relevant details were recorded. SPSS version 23 was used to analyse the data. Results: There were 155 patients in the study, with a mean age of 35±12 years; 95 (65.34%) were male and 60 (40.67%) were female. Forty-seven (32.0%) patients were incorrectly diagnosed by ER doctors and sent home as outpatients; fifty (33.33%) were treated by non-medical professionals such as chiropractic physicians, nurses, patients who self-medicated, spiritual healers, hakeems, and homoeopaths and thirty-two (21.33%) did not seek any medical attention at all during the initial attack of appendicitis. Lack of patient or family financial means was the leading cause of delay (45.34 percent of all cases). Conclusion: Early diagnosis and surgical intervention are critical for the effective care of acute appendicitis, which dramatically reduces complications, morbidity, and death of these patients. An immediate public education effort is required to encourage people to get the care they need at the right time and avoid difficulties. Keywords: Appendicitis, delayed appendicitis, appendicectomy, acute abdomen.